CRITICAL ANALYSIS OF THE CONVENTIONAL ECONOMIC SYSTEM - Ulil Amri (CV. Cendekiawan Muda Sriwijaya, 2024)
Critical analysis of conventional economic systems is an important study in understanding the challenges and weaknesses that may exist in the dominant economic models used today. Often conventional economic systems are based on the principles of capitalism and neoliberalism, which place a primary focus on economic growth, corporate profits, and market competition. However, this approach also faces criticism for causing economic inequality, environmental damage and worsening social inequality. Critical analysis of conventional economic systems includes in-depth evaluation of economic power structures, distribution of wealth, and their impact on society and the environment.